Comparative Ethnolinguistics on Metaphorical Interpretations in Japanese Kotowaza and Malay Proverbs - Muhammad Nadzif Bin Ramlan (Universitas Diponegoro, 2021)
This paper examines the comparison between Japanese kotowaza and Malay proverbs via the lens of ethnolinguistics. The rich cultural exchanges between the Japanese empire and Malay civilisation since the 15th century must be based on mutual values that both parties can agree upon. One such aspect is the sociocultural values apparent in proverbs and idioms. This aspect is integral in ethnolinguistics. Therefore, this paper has three objectives: 1) To compare and contrast the entities and the conventionalised metaphorical interpretations made in the proverbs of the two languages; 2) to conduct a comprehensive discourse analysis on the proverbs based on ethnolinguistic approaches; and 3) to trailblaze the opportunities for ethnolinguists to consider expanding the research in paremiology. This research is motivated due to the very scarce resource in Japanese-Malay comparative proverbs study. The methods used are library research and Cornell note-taking technique. There are 10 proverbs respectively in Japanese and Malay for similarity and 5 respective proverbs for the difference, totalling to 30 proverbs in both languages. The findings show that the proverbs in the two different languages can both reach the same interpretation despite different extensive backgrounds. However, opposing or dissimilar outcomes also occur despite the same referents or symbols used in the metaphors. This paper concludes with the limitations and suggestions for linguists to consider in their research on proverbs.